2016
DOI: 10.1037/abn0000149
|View full text |Cite
|
Sign up to set email alerts
|

Parasympathetic nervous system activity predicts mood repair use and its effectiveness among adolescents with and without histories of major depression.

Abstract: Depressive disorders that onset in the juvenile years have been linked to far reaching adverse consequences, making it imperative to elucidate key mechanisms and contributory factors. Excessive use of regulatory responses that exacerbate sadness (maladaptive mood repair) or insufficient use of regulatory responses that reduce it (adaptive mood repair) may reflect behavioral mechanisms of depression risk. Cardiac vagal control, indexed by patterns of respiratory sinus arrhythmia (RSA), has received attention as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 94 publications
3
42
2
Order By: Relevance
“…Likewise, Cribbett, Williams, Gunn, and Rau (2011) noted the incremental utility of combining RSA indices to predict adjustment during emotional stress. We have also found that patterns of RSA activity incrementally predict mental health outcomes, relative to single RSA indices (Yaroslavsky, Rottenberg, & Kovacs, 2013; Yaroslavsky et al, 2014). …”
Section: Measuring Pns Activitymentioning
confidence: 54%
“…Likewise, Cribbett, Williams, Gunn, and Rau (2011) noted the incremental utility of combining RSA indices to predict adjustment during emotional stress. We have also found that patterns of RSA activity incrementally predict mental health outcomes, relative to single RSA indices (Yaroslavsky, Rottenberg, & Kovacs, 2013; Yaroslavsky et al, 2014). …”
Section: Measuring Pns Activitymentioning
confidence: 54%
“…When combined with a lack of parasympathetic flexibility in response to a sad film, which may represent difficulty appropriately engaging with relevant stimuli, individuals may have a “double load” of difficulty adapting to situational demands. This physiological and cognitive burden could interfere with effective self-regulation (e.g., Yaroslavsky et al, 2016) and make them more susceptible to experiencing symptoms of depression when adaptation becomes necessary. Although the study did not evaluate neural networks, it is possible that difficulty with flexibly disengaging from self-referential thinking and attending to task-relevant stimuli are driven in part by dysfunctional activity within the default mode network.…”
Section: Discussionmentioning
confidence: 99%
“…These patterns are postulated to relate to poorer self regulation. Elsewhere, we have found that atypical patterns of resting RSA and RSA reactivity in youths with a history of juvenile onset depressed predicted deficits in mood repair, where mood repair refers to behaviors that decrease feelings of sadness or dysphoria (e.g., Josephson, Singer, & Salovey, 1996), as assessed by both trait measures and laboratory probes (Yaroslavsky et al, 2015). .).…”
mentioning
confidence: 99%